The orientalist mind on the lazy Malays stereotype: is it true? - Rojudin, Nur Aqilah; Noor Muhammad, Salmah Jan (Human Resource Management Academic Research Society, 2020)
The Western society hold onto the idea of living by seeing and believing in something logical through scientific proof in an action. Orientalists believe in realism and fully take into account the mind as an alternative of seeking factual knowledge that is clear and correct through thorough and continuous researches. However, this has created a typical stereotype on the characteristics of the Malay society in general. Therefore, this article will be focusing on the view from the Western society towards the Malay society through the typical mind of the orientalists, specifically on the concept of lazy Malays which is very synonymous among the Malay community itself. This research will be using the methods of comparison and content analysis to analyse the stereotype of lazy Malays concept through the mind of the orientalists and the Malays themselves. The results from this research suggested that the given view by the Western society regarding this concept does not entirely meant to be in a negative perspective as there are also positive perspectives given by the Western scholars on Malays’ way of living.